Planned delivery route of preterm breech singletons, and neonatal and 2‐year outcomes: a population‐based cohort study. (9th October 2018) - Lorthe, E; Sentilhes, L; Quere, M; Lebeaux, C; Winer, N; Torchin, H; Goffinet, F; Delorme, P; Kayem, G; ,
Abstract : Objective: To assess whether planned route of delivery is associated with perinatal and 2‐year outcomes for preterm breech singletons. Design: Prospective nationwide population‐based EPIPAGE‐2 cohort study. Setting: France, 2011. Sample: Three hundred and ninety women with breech singletons born at 26–34 weeks of gestation after preterm labour or preterm prelabour rupture of membranes. Methods: Propensity‐score analysis. Main outcome measures: Survival at discharge, survival at discharge without severe morbidity, and survival at 2 years of corrected age without neurosensory impairment. Results: Vaginal and caesarean deliveries were planned in 143 and 247 women, respectively. Neonates with planned vaginal delivery and planned caesarean delivery did not differ in survival (93.0 versus 95.7%, P  = 0.14), survival at discharge without severe morbidity (90.4 versus 89.9%, P  = 0.85), or survival at 2 years without neurosensory impairment (86.6 versus 91.6%, P  = 0.11). After applying propensity scores and assigning inverse probability of treatment weighting, as compared with planned vaginal delivery, planned caesarean delivery was not associated with improved survival (odds ratio, OR 1.31; 95% confidence interval, 95% CI 0.67–2.59), survival without severe morbidity (OR 0.75, 95% CI 0.45–1.27), or survival at 2 years without neurosensory impairment (OR 1.04, 95% CI 0.60–1.80). Results were similar after matching on propensity score. Conclusions: No association between planned caesarean delivery and improved outcomes for preterm breech singletons born at 26–34 weeks of gestation after preterm labour or preterm prelabour rupture of membranes was found. The route of delivery should be discussed with women, balancing neonatal outcomes with the higher risks of maternal morbidity associated with caesarean section performed at low gestational age. Tweetable abstract: Planned caesarean delivery is not associated with improved outcomes for breech singletons born at 26–34 weeks of gestation.